Group II metal complexes of the germylidendiide dianion radical and germylidenide anion - Chia, Siew-Peng (2014)
The two-electron reduction of a Group 14-element(I) complex [RË⋅] (E=Ge, R=supporting ligand) to form a novel low-valent dianion radical with the composition [RË:]. 2− is reported. The reaction of [LGeCl] (1, L=2,6-(CH[DOUBLE BOND]NAr)2C6H3, Ar=2,6-iPr2C6H3) with excess calcium in THF at room temperature afforded the germylidenediide dianion radical complex [LGe]. 2−⋅Ca(THF)32+ (2). The reaction proceeds through the formation of the germanium(I) radical [LGe⋅], which then undergoes a two-electron reduction with calcium to form 2. EPR spectroscopy, X-ray crystallography, and theoretical studies show that the germanium center in 2 has two lone pairs of electrons and the radical is delocalized over the germanium-containing heterocycle. In contrast, the magnesium derivative of the germylidendiide dianion radical is unstable and undergoes dimerization with concurrent dearomatization to form the germylidenide anion complex [C6H3-2-{C(H)[DOUBLE BOND]NAr}Ge-Mg-6-{C(H)-NAr}]2 (3).